‘Don’t Look Back, You Thief!’. Violence towards Convicted Criminals in Prisons in the Last Decade of Communist Poland - Szczepanik, Renata; Cieślikowska-Ryczko, Angelika (Acta Poloniae Historica, 2019)
This article seeks to reconstruct the victimisation of so-called ‘criminal’ prisoners at penitentiary facilities during the last decade of what was the People’s Republic of Poland (i.e. communist Poland). The introductory section outlines the context of the implemented and evolving penitentiary policy of the past years and the importance of the political system transformation for the organisation of the penitentiary system. The proposed analysis focuses on the violence experience in the relations of the convicted with the prison officers. The article describes the methods of building and reinforcing (inter)dependence relations founded upon various forms of violence – primarily, direct physical actions and the managing by the officers of poor social conditions that led to degrade and symbolically depersonalise the prisoners. The description, moreover, includes the strategies the inmates resorted to in dealing with the oppression they experienced. The analysis is based on interviews with multiple recidivists and autobiographical letters of prisoners who served time in the 1980s decade.